The Possible Role of Turbopause on Sporadic‐E Layer Formation at Middle and Low Latitudes - Qiong Tang; Chen Zhou; Huixin Liu; Yi Liu; Jiaqi Zhao; Zhibin Yu; Zhengyu Zhao; Xueshang Feng (Space Weather)
Abstract In this paper, we examine the mechanism of middle‐ and low‐latitude sporadic‐E (Es) layer formation. Observations of ionosondes and meteor radars at stations of different latitudes show that Es layer also formed at low‐altitude nonwindshear points, which is distinct from prototypical windshear theory. The theoretical modeling results show that metallic ions can effectively accumulate by the combined effect of the zonal and meridional winds in the mesosphere and the lower thermosphere region. Numerical simulation results also demonstrate that metallic ions can accumulate without wind shear at lower height (90–105 km) as a consequence of the MLT winds leading to the ion drifting downward. We suggest that the turbopause at 90–105 km plays an important role in forming low‐altitude Es layer in the middle‐ and low‐latitude regions.